The Experience of Social Service Provision to Older Adults With Schizophrenia in Housing Programs - Ogden, Lydia P. (International Journal of Psychosocial Rehabilitation, 2014)
This article reports on themes generated through phenomenological analysis of semi-structured interviews with seven social service providers experienced in working with older adults with schizophrenia in housing programs. Their services assure housing stability, however attributes of their work experience may affect implementation of effective services. Understand- ing of their work experience can develop and improve social service provision. Findings identify three essential themes: Providers conceptualize older adults with schizophrenia as “survivors;” providers saw these survivors aging into yet further hardships; providers engaged in a parallel process of struggling and coping with their work with these survivors. Discus- sion of the themes is presented with consideration of practice and policy implications.